PERLINDUNGAN JASA ASURANSI OLEH ORGANISASI IKATAN NOTARIS INDONESIA KEPADA PROFESI NOTARIS - , NURLITA NURLETTE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to understand a form of protection insurance given by Indonesian Notaries Association for notary profession, and to understand as a whole implementing protection mechanism of insurance services for notary profession. The used research method is a juridical-normative research which the researcher examine the norm, but it is not the norm in the regulations, but examine the implementation of the norm with a type of exploratory research